Evaluation of Water Quality for Greater Zab River by Principal Component Analysis/ Factor Analysis - Shekha, Yahya Ahmed (Iraqi Journal of Science, 2022)
This study was conducted to determining the variable effects on water quality of Greater Zab River in Erbil province, Iraq, using multivariate statistical analysis. Seventeen variables were monitored in four sampling sites during one year (from May 2012 to April 2013). The dataset were treated using principal component analysis (PCA)/ factor analysis (FA), cluster analysis (CA) to the most important factors affecting water quality, sources of pollution and suitability of water for drinking consumption and irrigation. Six factors were identified as responsible for the data structure explaining 73.5% of the total variance in the dataset and are conditionally named, hydrochemical from weathering, mineral salts and domestic wastes. CA showed two different groups of similarity between sampling sites, in which site 2 was more contaminated than other studied sites. Their pH and TDS values were found in agreement for drinking and irrigation purposes with drinking water quality standard for Iraq, WHO, and Richards standards. SAR contents were low and maximum value was observed at site 2 and all sites classified as S1 type (low salinity) water quality. While, sulfate concentration exceeding permissible level according to water quality standard for Iraqi standard for drinking water, and irrigation purposes Richards standards. Generally, results of most water quality parameters revealed that Greater Zab River were within permissible level for drinking water consumption, while it regarded as safe water type for all kinds of crops.